Research on multi-objective linear programming problem with fuzzy coefficients in constraints - Zhang, Guoli; Zuo, Hua (International journal of machine learning and cybernetics, 2014)
The concepts of Q-effective solution and effective solution are extended to the model of multi-objective linear programming problem with fuzzy coefficients in constraints. Q-effective solution and effective solution are defined as fuzzy sets. The degree of an element as Q-effective solution is uniquely determined, and it fully describes the degree of solution satisfying constraints. Further, the concept of effective solution is introduced. Finally, a numerical example is given to illustrate the difference between Q-effective solution and effective solution.